State-selective charge transfer cross sections for light ion impact of atomic hydrogen. (15th January 2015) - Schultz, D R; Stancil, P C; Havener, C C
Abstract: Owing to the utility of diagnosing plasma properties such as impurity concentration and spatial distribution, and plasma temperature and rotation, by detection of photon emission following capture of electrons from atomic hydrogen to excited states of multiply charged ions, new calculations of state-selective charge transfer involving light ions have been carried out using the atomic orbital close-coupling and the classical trajectory Monte Carlo methods. By comparing these with results of other approaches applicable in a lower impact energy regime, and by benchmarking them using key experimental data, knowledge of the cross sections can be made available across the range parameters needed by fusion plasma diagnostics.